Examining specific deterrence effects on DWI among serious offenders - Bouffard, Jeffrey A. (Crime & delinquency, 2017)
Deterrence research supports the idea that punishment curbs offending; however, results for the specific deterrent effects of drunk driving are more nuanced. This research is often limited in its use of non-offender samples, its failure to examine links between past sanctions and subsequent risk perceptions, and in its use of aggregate-level data, thereby precluding any exploration of individuals’ perceived sanction risks. The current study examines the relationship between 824 felony inmates’ experiences with formal legal sanctions for drunk driving and their risk perceptions for driving drunk as well as their hypothetical intentions to drive drunk. Results generally fail to support deterrence theory’s propositions, and instead uncover some positive punishment effects (higher drunk driving intentions among those sanctioned previously) net of important theoretical controls. Implications for subsequent research and policy making are presented.